(untitled) (Applied Biological Research, 2020)
The present study was aimed to assess the suitability of radiofrequency treated rice bran supplementation in wheat bread. The refined wheat flour was blended with radiofrequency stabilized rice bran in varying proportions (100:0, 95:5, 90:10, 85:15, 80:20, 75:25 and 70:30) and the formulated breads were assessed for their physicochemical and microbial characteristics. The bread with 30% stabilized rice bran supplementation showed highest crude protein (13.48%), crude fat (6.69%) and crude fiber (3.60%) contents, whereas control treatment(100% wheat flour) had lowest crude protein (11.64%), crude fat (2.43%) and crude fiber (1.56%) content. Loaf weight, redness (a*) and yellowness (b*) of the formulated breads increased with increase in stabilized rice bran; while loaf volume, specific volume, crust to crumb ratio and L* value decreased with the addition of stabilized rice bran. The supplementation of stabilized rice bran increased total bacterial and yeast and mould counts of bread from 2.84 × 104 to 3.19 × 104 and 1.49 × 104 to 1.84 × 104 cfu g-1, respectively. During storage period of 4 days, microbial count and yeast and mould count of breads increased from 0.34 × 104 to 6.41 × 104 and 0.25 × 104 to 3.32 × 104 cfu g-1, respectively. It may be concluded that supplementation of rice bran up 20% enhanced nutritional and overall acceptability scores.